Analysis of Investment Increase Contribution to GRDP In 2020 Central Java Province - Dyfan Jaya; Tony Kwok; Feryanto Marcus (Eduvest - Journal of Universal Studies, 2021)
One of the ways for the government to find out the level of economic growth is by calculating the value of national income, especially which is the focus of the government to be able to increase the per capita income of the community in each region so that it can contribute to local revenue which will also increase national income, the government's strategies and efforts to increase it. This research method uses descriptive analysis presented with statistical data, statistical data used in the form of tables, diagrams, graphs and others. Descriptive analysis using various sources of literature and articles as material for analyzing research problems to describe the investment contribution of Central Java province to increasing national income. The conclusion that can be drawn from the results of the analysis of the article is the strategy of the regional government of Central Java Province to increase local revenue and support efforts to increase national income through investment by setting up investment licensing regulations for both PMA/PMDN easily and transparently as well as promotion and training to increase regional investment figures, besides that the most important point to increase investment realization is the consistency of innovation and creativity of the government and the community to form new ideas that can compete with the global market.